(3JHjjf GdeYGbO hJaSjQ GdebGUOs - (3fajS Hf YhV , HQgGf GdOjf fajS Hf YhV Hf Mcje GdcQeGfj,J (B841 (3g` s
(3ChdgG (B:s
(3hGdUdGI hGdSdGe Ydi ef jOGhi HWH GdMbjbI ajbhd GdabjQ Edi Gddg JYGdi fajS Hf YhV s
(3BNQgG (B:s
(3hjJLGhR YfgG Edi ehVY GdhQe HYOq s
(3GdfU TQM dcJGH GdCSHGH hGdYdGeGJ deMeO Hf Ydi Hf YeQ GdSeQbfOis
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQM s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B44 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B114s
Keywords: (3GdWHs